2016
DOI: 10.1002/14651858.cd003067.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Pit and fissure sealants versus fluoride varnishes for preventing dental decay in the permanent teeth of children and adolescents

Abstract: Pit and fissure sealants versus fluoride varnishes for preventing dental decay in the permanent teeth of children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 52 publications
0
108
1
7
Order By: Relevance
“…The authors stated that the body of evidence was assessed as low. Ahovuo-Saloranta et al 16 concluded that the conclusion of the updated review remained the same as the last update in 2010, that is, as a result of the limited number of data available it is was not possible to draw clear conclusions about possible differences in effectiveness for preventing or controlling dental caries on occlusal surfaces of permanent molars.…”
Section: Fissure Sealant Versus Fluoride Varnishmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors stated that the body of evidence was assessed as low. Ahovuo-Saloranta et al 16 concluded that the conclusion of the updated review remained the same as the last update in 2010, that is, as a result of the limited number of data available it is was not possible to draw clear conclusions about possible differences in effectiveness for preventing or controlling dental caries on occlusal surfaces of permanent molars.…”
Section: Fissure Sealant Versus Fluoride Varnishmentioning
confidence: 99%
“…Ahovuo-Saloranta et al 16 have recently published a Cochrane systematic review on the relative effectiveness of FS versus FV. This updates a previous version of the review published in 2010.…”
Section: Fissure Sealant Versus Fluoride Varnishmentioning
confidence: 99%
See 2 more Smart Citations
“…During the study of the relation between occlusal surface morphology and its high probability to develop dental plaque accumulation, trapping of food deposits and bacterial colonization, It was thought that the bottom of the occlusal surface of pits and fissures were the first areas of bacterial invasion and colonization and their deep location responsible for inaccessibility of the bristle of tooth-brush to reach and clean. [9,10] , fig (1) So lack of good mechanical cleaning in the bottom of the fissure makes the control of plaque and food accumulation impossible, in addition to ill effect of fluoride application that will be so difficult to reach the bacteria embedded in that area. Studies revealed that many evidences confirmed that lateral walls of the fissures are the first sites that caries process begin and not at the bottom of the fissure.…”
Section: Discussionmentioning
confidence: 99%